Diagnosing and investigating adverse reactions in metal on metal hip implants. (29th November 2011) - Fary, Camdon; Thomas, Geraint Emyr Rhys; Taylor, Adrian; Beard, David; Carr, Andrew; Glyn-Jones, Sion
Abstract : Use of metal bearings in hip replacements and resurfacing operations has led to adverse reactions to metal debris in many patients. This article examines how to assess and manage any patient with a metal on metal total hip replacement who presents with potential joint failure